Author 
Topic 

newton
Junior Member
USA
4 Posts 
Posted  10/16/2007 : 11:26:41

I am trying to simplify the following equation:
((x+c)+y) + ((xc)+y) = 2a
to get: x/a + y/(a  c) = 1. I brought the second radical to the right side of the equation, squared and start simplifying:
(x+c)+y = 4a4a ((xc)+y) + (xc)+y (x+c)+y)  (xc)y = 4a  4a((xc)+y) (x+c)  (xc) = 4a4a((xc)+y) 4cx = 4a4a((xc)+y) cx = aa((xc)+y) cx  a = a((xc)+y)
How do I proceed from here, to get what I want above?



peppers18
Advanced Member
Canada
124 Posts 

Subhotosh Khan
Advanced Member
USA
9116 Posts 
Posted  10/16/2007 : 12:19:55

quote: Originally posted by newton
I am trying to simplify the following equation:
((x+c)+y) + ((xc)+y) = 2a
to get: x/a + y/(a  c) = 1. I brought the second radical to the right side of the equation, squared and start simplifying:
(x+c)+y = 4a4a ((xc)+y) + (xc)+y (x+c)+y)  (xc)y = 4a  4a((xc)+y) (x+c)  (xc) = 4a4a((xc)+y) 4cx = 4a4a((xc)+y) cx = aa((xc)+y) cx  a = a((xc)+y)<Square both sides again and simplify
However I get equation of hyperbola from there  check your signs How do I proceed from here, to get what I want above?

Edited by  Subhotosh Khan on 10/16/2007 12:32:53 


newton
Junior Member
USA
4 Posts 
Posted  10/16/2007 : 15:31:49

To peppers18. I checked the website. That is exactly what I was looking for. Thank you. 



Topic 
